Effect of grain size and grain content on the hardness and drillability of rocks - Mou Yang,; Yingfeng-Meng,; Gao Li,; Lin Han,; Yufei-Li, (Universiti Kebangsaan Malaysia, 2014)
It is well-known that the characteristics of hardness and drillability are influenced by microstructure of rock. In this study, rock properties were analyzed on grain size and grain content. Coarse-grain and fine-grain sandstones were tested under successive indentation condition. Eighteen groups of sandstone and shale were employed for the drillability test. Indentation tests results showed that grain size influenced the low point of residual hardness, the crushing depth and volume and grain content influenced the peak point of hardness. The drillability values of shale increased with increasing contents of clay and quartz. Meanwhile, drillability values of sandstone increased with increasing content of quartz, but decreased with increasing content of clay. Therefore, these preliminary studies show great potential applications for selecting suitable bit type and formulating drilling program as a function of rock microstructure and crushing rock method for bit in the oil drilling.